Mind the miscibility gap: Cation mixing and current density driven non-equilibrium phase transformations in spinel cathode materials - Gustafsson, Olof; Schökel, Alexander; Brant, William R. (Frontiers in Energy Research, 2022)
Cathode materials that exhibit phase transitions with large structural rearrangements during electrochemical cycling are generally seen as disadvantageous. Large volume changes and lattice mismatches between intermediate phases tend to lead to significant kinetic barriers, as well as strain and particle cracking. In this regard, solid solution reactions are more desirable as they provide lower energy barriers and no miscibility gap between co-existing phases. The high-voltage cathode material LiNi0.5Mn1.5O4 is an interesting candidate for high power and rate capability applications, however little is known on how its phase transitions occur on the particle level. In the presented work operando X-ray diffraction was utilized together with detailed peak profile analysis to elucidate the phase transition mechanism dependency on transition metal cation order and current density. When fully disordered, the material was found to undergo a bulk single-phase solid solution reaction between the intermediate phases LiNi0.44Mn1.56O4 and Li0.5Ni0.44Mn1.56O4 followed by a first order phase transition with a coherent interphase between the intermediates Li0.5Ni0.44Mn1.56O4 and Ni0.44Mn1.6O4. When fully ordered and slightly less ordered, two separate first order phase transitions with a coherent interphase between the same intermediate phases were observed. On discharge, the fast kinetics of the transition between Li0.5Ni0.44Mn1.56O4 and LiNi0.44Mn1.56O4 resulted in less strain on the former phase. For all samples the miscibility gap between the intermediate phases narrowed with increased current density, suggesting that the solid solution domain formed at the coherent interphase can be extended when the rate of (de)lithiation exceeds the movement speed of the interphase at the phase transition. This effect was found to be larger with increasing cation disorder. The influence of transition metal ordering on the ability to form solid solutions is in good agreement with computational phase diagrams of LiNi0.5Mn1.5O4, showing that disorder is important for promoting and stabilizing solid solutions. These results indicate that the degree of transition metal ordering within the material is of importance for obtaining a material with small lattice mismatches between the involved intermediate phases and for rational design of full solid solution materials.